Synergizing Islamic Ecotheology and Baduy Ecological Wisdom: A Framework for Sustainable Environmental Ethics - Omang Komarudin; Lukman Nugraha; Alam Tarlam; Sukatma Sukatma (UIN Sunan Gunung Djati Bandung, 2026)
The escalating global ecological crisis demands solutions that transcend mere technical fixes, drawing instead on the profound synergy between sacred religious values and deeply rooted indigenous wisdom. This study, pioneering in its examination of the integration of Islamic ecotheology with the centuries-old ecological traditions of the Baduy community, crafts a groundbreaking environmental ethics model tailored for contemporary Indonesia. Utilizing a qualitative narrative-comparative research design, insights were dynamically gathered through an immersive mix of literature reviews, field observations, in-depth interviews, and meticulous documentation. Subsequent thematic analysis uncovers a powerful, harmonious alignment between core Islamic concepts—such as khalīfah (stewardship), amānah (trust), and mīzān (cosmic balance)—and the foundational Baduy principles of pikukuh karuhun (ancestral mandates), strict ecological taboos, and sacred forest conservation. Remarkably, both value systems independently champion a shared ethos of deep moral responsibility, voluntary simplicity, and an absolute rejection of environmental exploitation. By weaving these two worldviews together, this research produces a highly holistic environmental ethics model that bridges divine religious legitimacy with time-tested, practical indigenous conservation methods. Rather than treating faith and tradition as static relics, this integrated framework revitalizes them into active catalysts for deep ecological awareness. Ultimately, this newly forged model offers transformative strategic potential, providing an authentic and culturally resonant blueprint to revolutionize environmental education, reshape grassroots policy development, and drive sustainable community empowerment initiatives across the nation.